Analisis kinerja keuangan PT Kereta Api Indonesia (Persero) dengan metode DuPont system - Rabbani, Rafid Azmi; Yasmin, Annisa; Nurita, Dea; Lestari, Lela (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
Company financial performance is a benchmark to increase the value of a company. The existence of Covid-19 pandemic has caused the economy in Indonesia to decline which has had an impact on the financial performance of several companies, one of which is PT KAI (Persero). This research aims to determine the financial performance of PT KAI (Persero) in 2016-2021 as measured through financial statement analysis using the DuPont system. The research method used is descriptive quantitative. The data source used is secondary data, in the form of PT KAI (Persero) financial reports in the form of time series. The analytical technique used is the DuPont system. The results showed that the financial performance of PT KAI (Persero) in 2016-2021 was in a good position. Fluctuating NPM has a major impact on ROE, resulting in PT KAI (Persero) having to be vigilant and immediately innovate because their financial performance is not yet stable enough. The company expected to be able to optimize their financial management, especially in increasing sales volume accompanied by a high level of net profit and good asset management to create a good NPM and TATO for the company's ROI and ROE.